1977
DOI: 10.2307/1938998
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Model for Decomposition in Grasslands

Abstract: A model has been developed to simulate the dynamics of decomposers and substrates in grasslands. Sub~trates r~presented are humic material, feces, and dead plant and animal remains. Exc~pt for humic ma~enal, sub_strates are fur!her divid_ed _into a rapidly and a slowly decomposing f~actwn. The proportiOn of rapidly decomposmg matenal m a substrate is predicted from its initial mtroge_n content. The bel_owground P?r~ion of ~he system is divided into layers because temperature and soil water.' the most Important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
10

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(60 citation statements)
references
References 56 publications
1
49
0
10
Order By: Relevance
“…Equation 1 is valid only for temperatures greater than 0 "C; we assumed that dW/dt =0 for T< 0 "C. Equation 1 was subsequently modified so as to distinguish between the decay of labile material and the persistence of refractory material. The need for a modification of decomposition models to include both labile and refractory parts was noted by Bunnell et al (1977), Hunt (1978), Heal et a/. Wieder &Lang (1982).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 1 is valid only for temperatures greater than 0 "C; we assumed that dW/dt =0 for T< 0 "C. Equation 1 was subsequently modified so as to distinguish between the decay of labile material and the persistence of refractory material. The need for a modification of decomposition models to include both labile and refractory parts was noted by Bunnell et al (1977), Hunt (1978), Heal et a/. Wieder &Lang (1982).…”
Section: Resultsmentioning
confidence: 99%
“…These processes are regulated by a complex array of variables; two of the most important factors are climate and substrate chemical quality. Climatic variables that influence decomposition include temperature, moisture, and evapotranspiration (Bunnell et al, 1977;Hunt, 1978;Meentemeyer, 1978;Howard & Howard, 1979;Boddy, 1983). Decomposition of litter has also been shown to be affected by such factors as the C:N ratio, initial nutrient levels, and ligninlignocellulose content (Witkamp, 1966;Fogel & Cromack, 1977;Godshalk & Wetzel, 1978;Aber & Melillo, 1980;Schlesinger & Hasey, 1981;Berg et al, 1982;Melillo et al, 1982;Hodson et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of nutrient availability with carbon sequestration in decomposition and terrestrial carbon cycle models may include the biomass of active and inactive microbial and detritivore decomposers. [6,32,33] However, in a study where 13 C-labelled detritus and prey biomass were artificially increased, the density response of detritivore Collembola was related to increase of detritus, while the observed stable density of predator spiders still gained energy from Collembola. [34] Oelbermann et al [34] concluded that such a lack of response to resource supplementation is not necessarily due to the absence of a trophic linkage, but may be caused by compensatory changes in mortality factors, such as cannibalism, intraguild predation or prey quality.…”
mentioning
confidence: 92%
“…A double, four-parameter exponential decay model (Equation (1)) [13] [20], simulating decomposers and substrates (labile and the recalcitrant constants) dynamics in grasslands, was used to describe the decay pattern. …”
Section: Decay Modelmentioning
confidence: 99%